To develop vires assignment model to enhance studentsâ€™ confidence and competence in vocational subjects - Nurul Chairani Rangkuti (Universitas Sarjanawiyata Tamansiswa, 2019)
The objective of this study is to develop assignment model for making practice report in the form of video by smartphone where students act as reporter (ViReS assignment model). This assignment model is implemented and able to enhance students' confidence and competence in vocational subjects. The research method used is Research and Development (RnD) with the model of ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The product from this research is syntax model with ViReS assignment model. The research result shows that ViReS assignment model can be applied as assignment model in the practical learning. Students' self-confidence increases after the implementation from a less appropriate category to a fairly appropriate category. Student competencies increase after the implementation of the â€œappropriate enoughâ€ category to be â€œappropriateâ€ category. Students give good respond to this assignment method.